ҚАРШИ ТОПОНИМЛАРИ ТАДҚИҚОТЧИСИ (Scientific journal of the Fergana State University, 2023)
In this article we are talking about the toponyms "Names of streets and makhallas of the city of Karshi", which have a special place in the study of toponymy of Uzbekistan, found in the Dictionary by Nafasov. A scientific evaluation of this work of the scientist devoted to the study of urban toponymy is given.